S100-Alarmins Are Essential Pilots of Postnatal Innate Immune Adaptation - Viemann, Dorothee (Frontiers in Immunology, 2020)
The restricted capacity of newborn infants to mount inflammatory responses towards microbial challenges has traditionally been linked to the high risk of septic diseases during the neonatal period. In recent years, substantial evidence has been provided that this characteristic of the neonatal immune system is actually a meaningful physiologic state that is based on specific transiently active cellular and molecular mechanisms and required for a favorable course of postnatal immune adaptation. The identification of physiologically high amounts of S100-alarmins in neonates has been one of the crucial pieces in the puzzle that contributed to the change of concept. In this context, innate immune immaturity could be redefined and assigned to the epigenetic silence of adult-like cell-autonomous regulation at the beginning of life. S100-alarmins represent an alternative age-specific mechanism of immune regulation that protects neonates from hyperinflammatory immune responses. Here we summarize how infants are provided with S100-alarmins and why these allow an uneventful clash between the innate immune system and the extrauterine world. The mode of action of S100-alarmins is highlighted including their tuning functions at multiple levels for establishing a state of homeostasis with the environment in the newborn individual.